(untitled) (Research, Society and Development, 2020)
Due to the high prevalence and mortality rates of cervical cancer, it is essential that strategies for the adhering to disease screening through the Pap smear are effectively adopted, and nurses are of paramount importance in this process of prevention and health promotion, bringing comprehensive and humanized care during the cytopathological examination. This article has as premise, to promote an integrative-qualitative review, being established the data collection as follows: selection of the database, filtering of texts, inclusion and exclusion criteria, categorization of studies and evaluation of selected studies, aiming to: Analyze the factors that prevent the access to prevention and screening programs, as well as identify the approaches of professionals who have been trained to act in this context. The study demonstrated disinformation on the part of women, discomfort, fear of preventive examination and the lack of preparation of the team in welcoming, guiding and attending them in a humanized way. Thus, it is suggested the elaboration of other studies on the subject, which identifies the strategies and efforts that are being gathered so that incidence rates decrease, and also, that the institutions responsible for training nursing professionals, reinforce the disciplines that address the theme in question.